The stress-buffering effects of functional social support on ambulatory blood pressure - Bowen, Kimberly S; Uchino, Bert N; Birmingham, Wendy; Carlisle, McKenzie; Smith, Timothy W; Light, Kathleen C (Health psychology, 2014)
Social support is a reliable predictor of cardiovascular health. According to the buffering hypothesis, stress is 1 mechanism by which support is able to affect physiological processes. However, most of the experimental evidence for the hypothesis comes from laboratory studies. Ambulatory blood pressure (ABP) protocols examine participants in their natural environment, where they are more likely to encounter personally relevant real-world stressors. Furthermore, prior work shows that examining support by its specific functional components reveals additional independent links to health. The current study aimed to examine the stress-buffering effects of functional social support on ABP. One hundred eighty-eight participants completed a 1-day ABP assessment along with measures of functional social support and both global perceived stress and momentary stress at time of reading. RESULTS indicated main effects for both stress measures. Global support, emotional, tangible, and informational support only moderated the effects of momentary stress, but not global stress, in predicting ABP. Informational support was the most consistent stress-buffering predictor of ABP, predicting both ambulatory systolic and diastolic blood pressure. The predicted values in ABP for informational support achieved health-relevant differences, emphasizing the value of examining functional support beyond global support alone.